2019
DOI: 10.1016/j.ijpharm.2019.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of a peptide autoantigen to gold nanoparticles for intradermally administered antigen specific immunotherapy

Abstract: Antigen specific immunotherapy aims to tolerise patients to specific autoantigens that are responsible for the pathology of an autoimmune disease. Immune tolerance is generated in conditions where the immune response is supressed and thus gold nanoparticles (AuNPs) are an attractive drug delivery platform due to their anti-inflammatory effects and their potential to facilitate temporal and spatial delivery of a peptide autoantigen in conjunction with pro-tolerogenic elements. In this study we have covalently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…We have recently demonstrated that gold NPs (Midacore™) (<5 nm hydrodynamic radius), conjugated to a peptide autoantigen, can be effectively delivered into the dermal and epidermal layers of human skin explants by MicronJet600™ hollow MNs and target local antigen-presenting cells. 20 This present study is the first published report exploring the in vivo pharmacokinetics and resulting systemic immune response following MN-mediated delivery of a poorly-soluble autoantigenic peptide conjugated to ultra-small gold NPs.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…We have recently demonstrated that gold NPs (Midacore™) (<5 nm hydrodynamic radius), conjugated to a peptide autoantigen, can be effectively delivered into the dermal and epidermal layers of human skin explants by MicronJet600™ hollow MNs and target local antigen-presenting cells. 20 This present study is the first published report exploring the in vivo pharmacokinetics and resulting systemic immune response following MN-mediated delivery of a poorly-soluble autoantigenic peptide conjugated to ultra-small gold NPs.…”
mentioning
confidence: 83%
“…Midacore™) with a gold core size of <5 nm were 110 synthesized and supplied by Midatech Pharma 20. NPs were 111 conjugated with each of the poorly-soluble HIP and BDC2.5mi-112 motope peptides as well as the highly-soluble ovalbumin 113 peptide, OTII, using custom-synthesized peptides with a thiol 114 propionic acid linker, in an amide linkage at the N terminal (-S 115 (CH2)2-CONH) (AmbioPharm Inc., North Augusta, SC, USA).…”
mentioning
confidence: 99%
“…On the other side of immunotherapy, the use of metal-based nanoparticles for immune response evasion has been explored to treat autoimmune diseases. Dul et al [177] conjugated an autoantigen, the PIC19-A3 peptide, with AuNPs for the treatment of type 1 diabetes. They showed that the uptake of the peptide-AuNP conjugates by dendritic cells (DCs) prevents subsequent T-cell priming and activation.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…In another research, Dul uses PIC19-A3 peptide which is under clinical evaluation for the treatment of T1D to form negatively charged AuNPs, and then employ a clinically approved microneedle delivery system, MicronJet600, to deliver AuNPs into human skin. in vitro experiments, AuNP-peptide compounds can spread rapidly and widely to the entire dermis and be absorbed by dendritic cells, thereby reducing their ability to activate naive T cells ( Figure 5; Dul et al, 2019). It could potentially be used to treat T1D and the team claimed that this work was currently undergoing clinical studies to determine whether the system could indeed serve as a platform for antigen-specific tolerance induction.…”
Section: Nps Combining With Antigen Peptidesmentioning
confidence: 99%